(untitled) (Palíndromo, 2015)
In our society, which has many social issues, the school can play an important role in the human formation by offering some teaching that can emphasize the de- velopment of sensitivity, integrating several fields of knowledge and encouraging social and emotional competences. According to texts of National Curriculum Analyses, edu- cation must be committed to citizenship, which means to consider social and envi- ronmental views as the subject of reflection. For this purpose education should be seen interconnected with the areas of human development responsible for triggering the sensitivity and the emotion: art and aesthe- tics. It is understood that the combination of education and art can help build up a better human society. This study analyzed a pro- gram of meaningful activities through Art in an elementary school with the objective of contributing to the human formation.